“People say you’re going home, but I don’t have a home”: Housing After Prison - Doyle, Caroline (International journal of offender therapy and comparative criminology, 2024)
Recidivism in Australia is high, especially in the Australian Capital Territory (ACT). While high-quality stable housing has been shown to reduce recidivism, people released from prison face many barriers in obtaining housing. This paper reports on a qualitative study exploring the housing experiences of 11 people released from prison in the ACT. Participants felt the importance of housing for reintegration and avoiding recidivism, but reported many challenges, including issues relating to lack of pre-release planning, income and employment, drug use, difficulties and delays with accessing social housing, and complying with parole or bail conditions. We recommend increased investment in services to assist people in prison with organizing housing before release. Furthermore, as housing is a foundational need for reintegration and drug use is high among the prison population in the ACT, Housing First initiatives may be the most appropriate model for providing accommodation and reducing recidivism.